Dealcoholized organic silicon sealant as well as preparation method and application thereof

By combining silicone sealants with specific flame retardants, coupling agents, crosslinkers and catalysts, the problem of thermal decomposition and combustion of silicone sealants in the prior art at high temperatures is solved, and good flame retardant properties, mechanical properties and adhesive properties are achieved, and are suitable for a variety of harsh environments.

CN119570438APending Publication Date: 2025-03-07GUANGZHOU JOINTAS CHEM
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411613835.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing silicone sealants have thermal decomposition, mechanical properties degraded and combustion risks at high temperatures, and the addition of traditional flame retardants will affect their structural and mechanical properties.

Method used

Dealcoholized silicone sealant is used to improve flame retardant, mechanical properties and adhesive properties by combining flame retardant (aluminum hydroxide, aluminum hypophosphate and silicon micropowder), coupling agent (γ-aminopropyltriethoxysilane, etc.), crosslinking agent (methyl trimethoxysilane, etc.) and catalyst (diisobutyl titanate) by combining flame retardant, mechanical properties and adhesive properties.

Benefits of technology

It realizes that silicone sealant maintains good flame retardant and mechanical properties at high temperatures, and is green and environmentally friendly, does not produce toxic gases, and is suitable for a variety of harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005131612630000101
    Figure BDA0005131612630000101
  • Figure BDA0005131612630000102
    Figure BDA0005131612630000102
  • Figure BDA0005131612630000111
    Figure BDA0005131612630000111
Patent Text Reader

Abstract

The invention belongs to the technical field of sealants, and particularly relates to a dealcoholized organosilicon sealant as well as a preparation method and application thereof. The organic silicon sealant is prepared from alpha, omega dihydroxy polydimethylsiloxane, a flame retardant, a cross-linking agent, a coupling agent and a catalyst, the flame retardant comprises aluminum hydroxide, aluminum hypophosphite and silica powder; the coupling agent is prepared from gamma-aminopropyl triethoxy silane, gamma-(2, 3-epoxypropoxy) propyl trimethoxy silane and bis-(gamma-trimethoxy silylpropyl) amine; the cross-linking agent is prepared from methyl trimethoxy silane, methyl vinyl dimethoxy silane and methyl triethoxy silane; the catalyst comprises ethyl acetoacetate and diisobutyl titanate. The flame retardant, the coupling agent and the cross-linking agent are compounded by adopting specific substances, meanwhile, specific types of catalysts are adopted, and all the components have a synergistic effect, so that the organic silicon sealant has good flame retardant property, mechanical property and adhesive property at the same time and is not prone to yellowing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sealants, and particularly relates to a dealcoholized organic silicon sealant and a preparation method and application thereof. Background Art

[0002] With the continuous development of electronic industry technology, the fire prevention awareness of human society has been continuously enhanced, and many industries have formulated corresponding standards for the fire prevention requirements in their fields. Silicone glue is often used as an organic silicone sealant. It is a compound with Si-O-Si bond as the main chain and silicon atoms connecting carbon and hydrogen or other organic groups as the side chain. It has good high and low temperature resistance, electrical insulation and physiological inertness. It has the functions of moisture-proof, corrosion-proof, shock-proof and dust-proof. It is widely used in construction, electronic appliances and other industries. However, the ordinary silicone glue used in most electrical appliances does not have flame retardant properties. Ordinary silicone glue will undergo thermal decomposition at above 200°C, and its mechanical properties will decrease. At higher temperatures, the colloid will powder or even burn, and release a lot of heat and toxic smoke, posing serious safety hazards. At present, most of the flame-retardant silicone glues sold on the market are decarboxylated and deoxime types. During the curing process of the colloid, strong irritating gases will be released, which are harmful to the human body and the environment.

[0003] In order to improve the flame retardant properties, traditional silicone flame retardant materials generally use additive flame retardants, mainly including magnesium hydroxide, halogen flame retardants, phosphorus-containing flame retardants, etc. In order to achieve the desired flame retardant effect, the amount of such additives added is generally large, and the addition of these additives often destroys the structure of silicone and affects its mechanical properties. Therefore, while improving the flame retardancy, it will inevitably reduce the mechanical properties of silicone.

[0004] Therefore, it is of great significance to develop a silicone sealant with good flame retardant and mechanical properties. Summary of the invention

[0005] The present invention aims to solve one or more technical problems existing in the above-mentioned prior art and at least provide a beneficial choice. Specifically, the present invention provides a dealcoholized organic silicon sealant, which has good flame retardant properties and mechanical properties, and has good bonding properties.

[0006] The inventive concept of the present invention: the organic silicon sealant of the present invention comprises α,ω dihydroxy polydimethylsiloxane, a flame retardant, a crosslinking agent, a coupling agent, and a catalyst; the flame retardant comprises aluminum hydroxide, aluminum hypophosphite, and silicon micropowder; the coupling agent comprises γ-aminopropyl triethoxysilane, γ-(2,3-epoxypropoxy)propyl trimethoxysilane, and bis-(γ-trimethoxysilylpropyl)amine; the crosslinking agent comprises methyl trimethoxysilane, methyl vinyl dimethoxysilane, and methyl triethoxysilane; the catalyst comprises diisobutyl ethyl acetoacetate titanate. The flame retardant, coupling agent, and crosslinking agent of the present invention are all compounded with specific substances, and a specific type of catalyst is used at the same time. The components work synergistically, so that the organic silicon sealant has good flame retardant properties, mechanical properties, and bonding properties, and is green and environmentally friendly.

[0007] Therefore, a first aspect of the present invention provides a dealcoholized organic silicone sealant.

[0008] Specifically, the dealcoholized organic silicone sealant includes α,ω dihydroxy polydimethylsiloxane, a flame retardant, a crosslinking agent, a coupling agent, and a catalyst;

[0009] The flame retardant comprises aluminum hydroxide, aluminum hypophosphite and silicon powder;

[0010] The coupling agent includes γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane and bis-(γ-trimethoxysilylpropyl)amine;

[0011] The crosslinking agent includes methyltrimethoxysilane, methylvinyldimethoxysilane and methyltriethoxysilane;

[0012] The catalyst includes ethyl acetoacetate and diisobutyl titanate.

[0013] Specifically, the flame retardants aluminum hydroxide, aluminum hypophosphite and silicon powder are all solid-phase flame retardants. Through the compound use of nano-inorganic particles, inorganic phosphorus flame retardants and silicon flame retardants, a dense metal oxide film and carbon layer are formed during the combustion process, which effectively isolates oxygen, produces a synergistic flame retardant effect, and greatly improves the flame retardant efficiency, so that it can meet the needs of a variety of harsh use environments. In addition, they do not produce toxic gases released by the combustion of halogen flame retardants during the combustion process, and are environmentally friendly and non-toxic. Aluminum hydroxide is the hydroxide of aluminum and an inorganic flame retardant with three functions of flame retardancy, smoke elimination and filling. Aluminum hydroxide decomposes into Al2O3 and water when heated. The heat absorption of this reaction is as high as 1967.2KJ / kg. Among them, the water generated by the reaction further suppresses the increase in the combustion temperature, and Al2O3 forms a protective film on the surface of the combustion object to block the entry of oxygen. In addition, the strong dehydrating substances produced by the combustion can form a dense carbon layer to prevent the spread of the flame and achieve a flame retardant effect. Aluminum hypophosphite is an inorganic phosphorus flame retardant with high phosphorus content and excellent thermal stability. It produces aluminum phosphate, oxygen, water vapor and other substances under high temperature combustion, which can consume oxygen in the flame, thereby inhibiting the combustion of the flame and has excellent flame retardant properties. Silica powder is a silicon flame retardant, the main component of which is silicon dioxide. It has high stability and high temperature resistance, can resist high temperature heat sources, and its high thermal conductivity can also consume heat sources to inhibit combustion, thereby achieving a flame retardant effect. In addition, the use of aminosilane coupling agent to treat silica powder makes it easy to disperse and process, and there is basically no thickening phenomenon when used in silicone glue.

[0014] Specifically, the crosslinking agent adopts a blend system of methyltrimethoxysilane, methylvinyldimethoxysilane and methyltriethoxysilane, which can avoid the excessive crosslinking density caused by adding methyltrimethoxysilane alone, resulting in cracking of the silicone sealant during curing. At the same time, the compound use of the crosslinking agent can also improve the bonding performance and weather resistance of the silicone sealant.

[0015] Specifically, the coupling agent is a compound of γ-aminopropyltriethoxysilane (KH-550), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560) and bis-(γ-trimethoxysilylpropyl)amine. KH-550 can improve the adhesion of silicone sealant to inorganic materials such as metals, while KH-560 can improve the surface adhesion performance of organic materials and inorganic materials. Bis-(γ-trimethoxysilylpropyl) hydrolyzes to produce more hydroxyl groups, and has a higher cross-linking density after hydrolysis, which improves the adhesion to inorganic substrates such as metals and glass. The compound use of the three, on the one hand, enhances the wettability of silicone sealant on the surface of various substrates, and on the other hand, improves the universality of bonding to various substrates, thereby greatly improving the extensive bonding of silicone sealant and allowing it to be applied to more usage scenarios.

[0016] Specifically, the catalyst is diisobutyl acetoacetate titanate, which is very sensitive to moisture and can react quickly when exposed to water vapor at room temperature, thereby reducing the surface drying time of the silicone sealant, enhancing the storage stability of the silicone sealant, and improving its anti-yellowing ability.

[0017] In short, through the synergistic effect of the above components, the silicone sealant has good flame retardant properties, mechanical properties and bonding properties, and is green and environmentally friendly.

[0018] Preferably, in the flame retardant, the mass ratio of the aluminum hydroxide, aluminum hypophosphite and silicon micropowder is (1.6-2.5):(0.8-1.2):1; further preferably, in the flame retardant, the mass ratio of the aluminum hydroxide, aluminum hypophosphite and silicon micropowder is (1.8-2.2):(0.9-1.1):1; further preferably, in the flame retardant, the mass ratio of the aluminum hydroxide, aluminum hypophosphite and silicon micropowder is 2:1:1.

[0019] Preferably, in the coupling agent, the mass ratio of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and bis-(γ-trimethoxysilylpropyl)amine is (1.6-2.5):1:(1.6-2.5); further preferably, in the coupling agent, the mass ratio of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and bis-(γ-trimethoxysilylpropyl)amine is (1.8-2.2):1:(1.8-2.2); further preferably, in the coupling agent, the mass ratio of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and bis-(γ-trimethoxysilylpropyl)amine is 2:1:2.

[0020] Preferably, in the cross-linking agent, the mass ratio of the methyltrimethoxysilane, methylvinyldimethoxysilane and methyltriethoxysilane is (1.6-2.5):(0.8-1.2):1; further preferably, in the cross-linking agent, the mass ratio of the methyltrimethoxysilane, methylvinyldimethoxysilane and methyltriethoxysilane is (1.8-2.2):(0.9-1.1):1; further preferably, in the cross-linking agent, the mass ratio of the methyltrimethoxysilane, methylvinyldimethoxysilane and methyltriethoxysilane is 2:1:1.

[0021] Preferably, the aluminum hydroxide is unimodal aluminum hydroxide.

[0022] Specifically, the unimodal aluminum hydroxide has a uniform particle size distribution, excellent dispersion effect, is easy to be used in combination with other flame retardants, has excellent stability, and does not produce sedimentation, agglomeration, etc. during long-term storage.

[0023] Preferably, the organic silicone sealant comprises, by weight, 90-220 parts of α,ω dihydroxy polydimethylsiloxane, 90-220 parts of flame retardant, 9-33 parts of crosslinking agent, 1.8-16 parts of coupling agent, and 0.2-5.5 parts of catalyst.

[0024] Further preferably, the organic silicone sealant comprises, by weight, 100-200 parts of α,ω dihydroxy polydimethylsiloxane, 100-200 parts of flame retardant, 10-30 parts of crosslinking agent, 2-15 parts of coupling agent, and 0.2-5 parts of catalyst.

[0025] Preferably, the organic silicone sealant further comprises at least one of a filler and a plasticizer.

[0026] Preferably, the organic silicone sealant also includes a filler and a plasticizer; and by weight, the organic silicone sealant includes 90-220 parts of α,ω dihydroxy polydimethylsiloxane, 90-220 parts of flame retardant, 9-33 parts of cross-linking agent, 1.8-16 parts of coupling agent, 0.2-5.5 parts of catalyst, 45-110 parts of filler, and 9-22 parts of plasticizer.

[0027] Further preferably, the silicone sealant also includes a filler and a plasticizer; and in parts by weight, the silicone sealant includes 100-200 parts of α,ω dihydroxy polydimethylsiloxane, 100-200 parts of flame retardant, 10-30 parts of cross-linking agent, 2-15 parts of coupling agent, 0.2-5 parts of catalyst, 50-100 parts of filler, and 10-20 parts of plasticizer.

[0028] Preferably, at 25°C, the viscosity of the α,ω dihydroxy polydimethylsiloxane is 900-55000cps; further preferably, at 25°C, the viscosity of the α,ω dihydroxy polydimethylsiloxane is 1000-50000cps; further preferably, at 25°C, the viscosity of the α,ω dihydroxy polydimethylsiloxane is selected from 1000cps, 1500cps, 5000cps, 20000cps or 50000cps.

[0029] Preferably, the filler comprises heavy calcium carbonate treated with stearic acid and nano calcium carbonate treated with stearic acid.

[0030] Specifically, the heavy calcium carbonate and nano calcium carbonate in the filler are activated by stearic acid, and have finer particle size, more stable structure, and better dispersibility, which improves its processing performance. In addition, it can also give the silicone sealant good thixotropy to meet various complex dispensing construction environments, and has toughening and reinforcing effects, improves mechanical properties, and can also reduce costs, ensuring that the silicone sealant has good flame retardant properties and excellent mechanical properties.

[0031] Preferably, the plasticizer comprises dimethyl silicone oil.

[0032] Preferably, at 25°C, the viscosity of the dimethyl silicone oil is 100-1000cps; further preferably, at 25°C, the viscosity of the dimethyl silicone oil is 100-1000cps; further preferably, at 25°C, the viscosity of the dimethyl silicone oil is 100cps or 1000cps.

[0033] The second aspect of the present invention provides a method for preparing the organic silicon sealant described in the first aspect of the present invention.

[0034] Specifically, the preparation method of the organic silicon sealant comprises the following steps:

[0035] The raw material components are mixed to prepare the organic silicon sealant.

[0036] Preferably, the method for preparing the organic silicone sealant comprises the following steps:

[0037] (1) mixing and dispersing the α,ω-dihydroxypolydimethylsiloxane, filler, plasticizer and flame retardant to obtain a mixture;

[0038] (2) first cooling the mixture obtained in step (1), then adding the crosslinking agent, coupling agent and catalyst, and dispersing them to obtain the organic silicone sealant.

[0039] Preferably, in step (1), the degree of vacuum of the dispersion is less than or equal to -0.08 MPa, the temperature of the dispersion is 100-140°C, and the time of the dispersion is 1.5-3.5 h; further preferably, in step (1), the degree of vacuum of the dispersion is less than or equal to -0.09 MPa, the temperature of the dispersion is 110-130°C, and the time of the dispersion is 2-3 h.

[0040] Preferably, in step (2), the temperature is lowered to below 38°C; further preferably, in step (2), the temperature is lowered to below 35°C.

[0041] Preferably, in step (2), the crosslinking agent, coupling agent and catalyst are added step by step in sequence, and stirring and dispersing are performed after each step, and the stirring and dispersing time is 18-33 minutes; further preferably, the stirring and dispersing time is 20-30 minutes.

[0042] Preferably, in step (2), the degree of vacuum of the dispersion is less than or equal to -0.08 MPa. More preferably, in step (2), the degree of vacuum of the dispersion is less than or equal to -0.09 MPa.

[0043] The third aspect of the present invention provides a use of the organosilicon sealant described in the first aspect of the present invention in the field of sealing or fire protection.

[0044] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:

[0045] (1) The flame retardant, coupling agent and cross-linking agent of the present invention are all compounded with specific substances, and a specific type of catalyst is used. The components work synergistically, so that the silicone sealant has good flame retardant properties, mechanical properties and adhesive properties, and is green and environmentally friendly.

[0046] (2) The heavy calcium carbonate and nano calcium carbonate in the filler of the present invention are activated by stearic acid, which can give the silicone sealant good thixotropy, meet various complex dispensing construction environments, and have toughening and reinforcing effects, improve mechanical properties, and ensure that the sealant has good flame retardant properties while also having excellent mechanical properties. In addition, its fine particle size, stable structure, and better dispersibility can improve its processing performance. DETAILED DESCRIPTION

[0047] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0048] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0049] The sources of the relevant raw materials in the examples and comparative examples of the present invention are as follows:

[0050] Silica powder: purchased from Guangdong Jinge New Materials Co., Ltd., model FCJ-603.

[0051] Heavy calcium carbonate treated with stearic acid: purchased from Guangxi Hezhou Kelong Powder Co., Ltd., model TC10.

[0052] Nano-calcium carbonate treated with stearic acid: purchased from Guangxi Huana New Materials Co., Ltd., model number is CCR-2.

[0053] Example 1

[0054] A dealcoholized organic silicone sealant comprises, by weight, 100 parts of α,ω-dihydroxy polydimethylsiloxane with a viscosity of 1500cps at 25°C, 100 parts of a flame retardant (the mass ratio of unimodal aluminum hydroxide, aluminum hypophosphite and silicon micropowder is 2:1:1), 60 parts of heavy calcium carbonate treated with stearic acid, 20 parts of nano calcium carbonate treated with stearic acid, 10 parts of dimethyl silicone oil as a plasticizer with a viscosity of 100cps at 25°C, 10 parts of a crosslinking agent (the mass ratio of methyltrimethoxysilane, methylvinyldimethoxysilane and methyltriethoxysilane is 2:1:1), 3 parts of a coupling agent (the mass ratio of KH-550, KH-560 and bis-(γ-trimethoxysilylpropyl)amine is 2:1:2), and 2 parts of a catalyst, ethyl acetoacetate diisobutyl titanate.

[0055] The method for preparing a dealcoholized organosilicon sealant comprises the following steps:

[0056] α,ω-dihydroxypolydimethylsiloxane, flame retardant, heavy calcium carbonate treated with stearic acid, nano calcium carbonate treated with stearic acid, and plasticizer are added to a dynamic mixer respectively, and evacuated to a vacuum degree of -0.09MPa. Under vacuum conditions, dehydrate at 120°C and disperse with high-speed stirring for 3h, with an orbital speed of 1500rpm and a dispersion speed of 1500rpm. Then, the mixture is cooled to a temperature below 40°C, and a crosslinking agent, a coupling agent, and a catalyst are added step by step. Each step is vacuumed (vacuum degree of -0.09MPa) and stirred for 30min. After stirring and dispersing evenly, the mixture is discharged, with an orbital speed of 1000rpm and a dispersion speed of 500rpm to obtain a dealcoholized silicone sealant.

[0057] Example 2

[0058] The only difference between Example 2 and Example 1 is that in Example 2, the addition amount of heavy calcium carbonate treated with stearic acid is 70 parts, and the addition amount of nano calcium carbonate treated with stearic acid is 30 parts, and the rest is the same as Example 1.

[0059] Example 3

[0060] The only difference between Example 3 and Example 1 is that in Example 3, the addition amount of heavy calcium carbonate treated with stearic acid is 35 parts, and the addition amount of nano calcium carbonate treated with stearic acid is 15 parts, and the rest is the same as Example 1.

[0061] Example 4

[0062] The only difference between Example 4 and Example 1 is that the added amount of the catalyst ethyl acetoacetate diisobutyl titanate in Example 4 is 4 parts, and the rest is the same as Example 1.

[0063] Example 5

[0064] The only difference between Example 5 and Example 1 is that no plasticizer dimethyl silicone oil is added in Example 5, and the rest is the same as Example 1.

[0065] Comparative Example 1

[0066] The only difference between Comparative Example 1 and Example 1 is that no silicon powder is added to the flame retardant of Comparative Example 1, and the added amounts of unimodal aluminum hydroxide and aluminum hypophosphite are 100 parts, with a mass ratio of 2:1, and the rest are the same as Example 1.

[0067] Comparative Example 2

[0068] The only difference between Comparative Example 2 and Example 1 is that no aluminum hypophosphite is added to the flame retardant of Comparative Example 2, and the added amounts of unimodal aluminum hydroxide and silicon micropowder are 100 parts, with a mass ratio of 2:1, and the rest are the same as Example 1.

[0069] Comparative Example 3

[0070] The only difference between Comparative Example 3 and Example 1 is that no unimodal aluminum hydroxide is added to the flame retardant of Comparative Example 3, and the added amounts of aluminum hypophosphite and silicon micropowder are 100 parts, with a mass ratio of 1:1, and the rest are the same as Example 1.

[0071] Comparative Example 4

[0072] The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 uses an equal amount of ammonium polyphosphate to replace aluminum hypophosphite, and the rest is the same as Example 1.

[0073] Comparative Example 5

[0074] The difference between Comparative Example 5 and Example 1 is that no flame retardant is added in Comparative Example 5, and the other aspects are the same as Example 1.

[0075] Comparative Example 6

[0076] The only difference between Comparative Example 6 and Example 1 is that no methylvinyldimethoxysilane is added to the crosslinking agent of Comparative Example 6, and the mass ratio of methyltrimethoxysilane to methyltriethoxysilane is 2:1, and the added amount is 10 parts. The rest is the same as Example 1.

[0077] Comparative Example 7

[0078] The only difference between Comparative Example 7 and Example 1 is that the crosslinking agent of Comparative Example 7 uses methyltrimethoxysilane, phenyltrimethoxysilane and methyltriethoxysilane in a mass ratio of 2:1:1, and the added amount is 10 parts. The rest is the same as Example 1.

[0079] Comparative Example 8

[0080] The only difference between Comparative Example 8 and Example 1 is that no bis-(γ-trimethoxysilylpropyl)amine is added to the coupling agent of Comparative Example 8, and the mass ratio of KH-550 to KH-560 is 2:1, and the added amount is 3 parts in total. The rest is the same as Example 1.

[0081] Comparative Example 9

[0082] The only difference between Comparative Example 9 and Example 1 is that the coupling agent of Comparative Example 9 uses KH-550, KH-560 and (3-aminopropyl)trimethoxysilane in a mass ratio of 2:1:2, and the addition amount is 3 parts. The rest is the same as Example 1.

[0083] Comparative Example 10

[0084] The only difference between Comparative Example 10 and Example 1 is that the catalyst of Comparative Example 10 uses an equal amount of titanate compound D62 to replace diisobutyl acetoacetate ethyl titanate, and the rest is the same as Example 1.

[0085] Performance Testing

[0086] The performance tests were conducted on the organic silicon sealants prepared in Examples 1-5 and Comparative Examples 1-10. The specific test items and test methods are as follows:

[0087] (1) Flame retardant properties: The test was conducted in accordance with GB / T2408-2008. The silicone sealants prepared in Examples 1-5 and Comparative Examples 1-10 were prepared into test pieces in accordance with GB / T2408-2008 using a vertical combustion method. The test pieces had a size of (125±5) mm×(13.0±0.3) mm×(3.0±0.2) mm. Five test pieces were prepared and then tested after curing for 7 days under standard conditions.

[0088] (2) Surface drying time test: The test was conducted in accordance with GB / T 13477.5. At a temperature of 25±2°C and a relative humidity of 50±5%, the silicone sealants prepared in Examples 1-5 and Comparative Examples 1-10 were squeezed onto the surface of a plastic film with a thickness of about 2-3 mm and a length of >100 mm. Every 1 minute, the adhesive layer was lightly touched with a finger until the adhesive no longer stained the finger. The time from squeezing out to no longer sticking to the finger was recorded as the surface drying time.

[0089] (3) Tensile strength test: The test was conducted in accordance with GB / T 528-2009. A tensile specimen with a thickness of 2 mm was prepared on a polytetrafluoroethylene plate and the test was conducted after curing at 25°C ± 2°C for 7 days.

[0090] (4) High temperature aging yellowing test: The silicone sealants prepared in Examples 1-5 and Comparative Examples 1-10 were sealed in 300 mL plastic tubes, respectively, and placed in a forced air drying oven at 70°C ± 2°C for 7 days. The yellowing and aging of the appearance of the sealants were observed.

[0091] (5) Adhesion performance test: The test was conducted in accordance with GB 16776-2005. After wiping the surface of the substrate (the substrates were polycarbonate (PC), polyvinyl chloride (PVC), polyethylene terephthalate (PET), printed circuit board (PCB), Al, and 304 stainless steel), glue was dispensed on the surface of the substrate to obtain a 1.5 mm thick adhesive strip. The adhesion performance was tested after curing for 7 days at 25°C ± 2°C and a relative humidity of 50 ± 5%.

[0092] The test results of flame retardancy, surface drying time, tensile strength, yellowing after aging, and appearance characteristics after curing at room temperature of the silicone sealants prepared in Examples 1-5 and Comparative Examples 1-10 are shown in Table 1.

[0093] The test results of the adhesive properties of the silicone sealants prepared in Examples 1-5 and Comparative Examples 1-10 to various substrates are shown in Table 2.

[0094] Table 1: Test results of flame retardancy, surface drying time, tensile strength, yellowing after aging, and appearance characteristics after curing at room temperature of the silicone sealants prepared in Examples 1-5 and Comparative Examples 1-10

[0095]

[0096] Table 2: Test results of the adhesive properties of the silicone sealants prepared in Examples 1-5 and Comparative Examples 1-10 to various substrates

[0097]

[0098]

[0099] It can be seen from Table 1 and Table 2 that the organosilicon sealant of the present invention has good flame retardancy and mechanical properties, has good bonding properties to substrates such as PC, PVC, Al, and 304 stainless steel, can achieve good sealing effect, has a suitable surface drying time, has good anti-aging and yellowing effect, and is not easy to cure and crack.

[0100] Comparative Example 1 does not add silicon powder, Comparative Example 2 does not add aluminum hypophosphite, and Comparative Example 3 does not add unimodal aluminum hydroxide, so the flame retardant properties of Comparative Examples 1-3 are significantly worse than those of Example 1, and the mechanical properties also decrease to a certain extent. This shows that the unimodal aluminum hydroxide, aluminum hypophosphite and silicon powder in the flame retardant of the present invention have a synergistic effect, and the three work together to produce a synergistic flame retardant effect, isolate oxygen, and generate a dense metal oxide film and a dense carbon layer, thereby achieving a FV0 flame retardant grade, so that the silicone sealant can take into account both flame retardant properties and mechanical properties.

[0101] Comparative Example 4 uses an equal amount of ammonium polyphosphate to replace aluminum hypophosphite, so that the flame retardant performance of Comparative Example 4 is significantly worse than that of Example 1, and the mechanical properties also decrease to a certain extent. This shows that only by using a specific type of aluminum hypophosphite for compounding can the silicone sealant have both flame retardant and mechanical properties.

[0102] In comparative example 6, no methylvinyldimethoxysilane was added to the crosslinking agent, so that the surface drying time of comparative example 6 was too short, and the phenomenon of curing cracking occurred. This is because the addition of methylvinyldimethoxysilane with double bonds can avoid the crosslinking density of the entire system being too high, thereby avoiding the phenomenon of too short surface drying time of the glue sample and curing cracking. At the same time, there is interface damage between it and the 304 stainless steel substrate, indicating that its bonding performance is worse than that of Example 1, and then the sealing performance is worse than that of Example 1. In addition, the crosslinking agent of comparative example 7 uses methyltrimethoxysilane, phenyltrimethoxysilane and methyltriethoxysilane, and the surface drying time is slightly faster, and the phenomenon of curing cracking occurs, and the bonding performance is also worse than that of Example 1. The above explanation uses methyltrimethoxysilane and methyltriethoxysilane and needs to be compounded with methylvinyldimethoxysilane as a crosslinking agent so that the silicone sealant has a suitable surface drying time, is not easy to cure and crack, and has good bonding performance.

[0103] No bis-(γ-trimethoxysilylpropyl)amine was added to the coupling agent of Comparative Example 8, so that the interface between Comparative Example 8 and PVC, PET and 304 stainless steel substrates was damaged, indicating that the bonding performance of Comparative Example 8 was significantly worse than that of Example 1, and thus the sealing performance was significantly worse than that of Example 1. In Comparative Example 9, KH-550, KH-560 and (3-aminopropyl)trimethoxysilane were used as coupling agents, and the bonding performance was also significantly weakened compared with Example 1, indicating that the sealing performance was poor and the application scenarios were also limited. It is shown that the use of specific bis-(γ-trimethoxysilylpropyl)amine compounded with KH550 and KH560 can improve the bonding performance of silicone sealant with different substrates, so that the silicone sealant has good bonding performance for many substrates.

[0104] Comparative Example 10 uses titanate compound D62 as a catalyst, so that Comparative Example 10 turns yellow in the high temperature aging yellowing test, and the tensile strength is lower than that of Example 1. This shows that the selection of a specific catalyst can improve the storage stability of the silicone sealant, making it less prone to aging yellowing, and can help improve the mechanical properties to a certain extent.

[0105] In summary, the flame retardant, coupling agent and cross-linking agent of the present invention are all compounded with specific substances, and a specific type of catalyst is used. The components work synergistically, so that the silicone sealant has good flame retardant properties, mechanical properties and bonding properties, and is not prone to yellowing.

[0106] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A silicone sealant, characterized in that: Including α,ω-dihydroxy polydimethylsiloxane, flame retardant, crosslinking agent, coupling agent, catalyst; The flame retardant comprises aluminum hydroxide, aluminum hypophosphite and silicon powder; The coupling agent includes γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane and bis-(γ-trimethoxysilylpropyl)amine; The crosslinking agent includes methyltrimethoxysilane, methylvinyldimethoxysilane and methyltriethoxysilane; The catalyst includes ethyl acetoacetate and diisobutyl titanate.

2. The organic silicon sealant according to claim 1, characterized in that: In the flame retardant, the mass ratio of aluminum hydroxide, aluminum hypophosphite and silicon powder is (1.6-2.5): (0.8-1.2): 1; And / or, in the coupling agent, the mass ratio of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and bis-(γ-trimethoxysilylpropyl)amine is (1.6-2.5):1:(1.6-2.5); And / or, in the cross-linking agent, the mass ratio of methyltrimethoxysilane, methylvinyldimethoxysilane and methyltriethoxysilane is (1.6-2.5):(0.8-1.2):

1.

3. The organic silicon sealant according to claim 1, characterized in that: In parts by weight, the organic silicon sealant comprises 90-220 parts of α,ω-dihydroxypolydimethylsiloxane, 90-220 parts of flame retardant, 9-33 parts of crosslinking agent, 1.8-16 parts of coupling agent and 0.2-5.5 parts of catalyst.

4. The organic silicon sealant according to any one of claims 1 to 3, characterized in that: The organic silicon sealant further comprises at least one of a filler and a plasticizer.

5. The organic silicon sealant according to claim 4, characterized in that: The organic silicone sealant also includes fillers and plasticizers; and by weight, the organic silicone sealant includes 90-220 parts of α,ω-dihydroxypolydimethylsiloxane, 90-220 parts of flame retardant, 9-33 parts of cross-linking agent, 1.8-16 parts of coupling agent, 0.2-5.5 parts of catalyst, 45-110 parts of fillers, and 9-22 parts of plasticizer.

6. The organic silicon sealant according to claim 4, characterized in that: The filler includes heavy calcium carbonate treated with stearic acid and nano calcium carbonate treated with stearic acid; and / or the plasticizer includes dimethyl silicone oil.

7. The method for preparing the organosilicon sealant according to any one of claims 1 to 6, characterized in that: The following steps are involved: The raw material components are mixed to prepare the organic silicon sealant.

8. The preparation method according to claim 7, characterized in that: The following steps are involved: (1) mixing and dispersing the α,ω-dihydroxypolydimethylsiloxane, filler, plasticizer and flame retardant to obtain a mixture; (2) first cooling the mixture obtained in step (1), then adding the crosslinking agent, coupling agent and catalyst, and dispersing them to obtain the organic silicone sealant.

9. The preparation method according to claim 8, characterized in that: In step (1), the degree of vacuum during dispersion is less than or equal to -0.08 MPa, the temperature during dispersion is 100-140° C., and the time during dispersion is 1.5-3.5 h; And / or, in step (2), the temperature is lowered to below 38°C.

10. Use of the organosilicon sealant according to any one of claims 1 to 6 in the field of sealing or fire protection.

Citation Information

Cited By

  • Continuous pouring flame-retardant acrylic plate and preparation method thereof

    CN120904611A